PolliRS: A 3D-printed Pollicization Retractor System that Improves Access and Autonomy during the Surgical Procedure. Issue 6 (June 2021) - Papavasiliou, Theodora; Chatzimichail, Stelios; Yoshimura, Ryo; Sivakumar, Branavan
Abstract : Summary: We demonstrate the design, manufacture, and deployment of the first custom-made 3-dimensional (3D)-printed hand retractor for the pollicization procedure. Radiological images of the patient's hand were taken preoperatively to measure anatomical dimensions and guide the design of the device in a patient-precise manner. The 3D-printed, sterilizable, device was autoclaved and successfully used on a patient that underwent a pollicization procedure in our unit. The radiolucency of the device and the fluency enabled by the ability to exchange between different positions demonstrated the potential of this device in increasing the overall autonomy afforded to the lead-surgeon during the operation and demonstrated the potential of rapid-prototyping techniques such as 3D printing for producing patient-precise tools on-the-fly that taken account the specific needs of the patient.